The combination of miniaturized GPS/VHF tags and soluble backpack harness as an effective method for tracking lightweight and elusive birds - Pedro Sáez‐Gómez; Cristian Pérez-Granados; Germán M. López-Iborra (Journal of Avian Biology, 2025)
The use of global positioning system (GPS) tags is increasingly widespread for wildlife tracking in many ecological studies. However, GPS tags are often too heavy for lightweight species or require recapturing the animal to download the data. In this study, we designed a water‐soluble backpack harness linked to a handmade GPS+VHF tag combination to obtain GPS data without the need to recapture the animal. Once the harness disintegrates after rainfall, the GPS+VHF tags can be located via radiotracking, and the dataset can be downloaded. Specifically, we 1) assessed the most effective way to attach the VHF tag to the GPS (to minimize data loss in terms of quantity and quality), 2) tested effects on wild birds, and 3) evaluated the efficiency of device retrieval by tagging Dupont's larks Chersophilus duponti, a small (~ 40 g), elusive passerine. Results showed that the VHF tag should be attached to the GPS at a 45º angle to avoid negative effects on GPS data. To reduce GPS location error, we recommend using data obtained with ≥ 5 satellites and, ideally, > 7 satellites, for average errors less than 10 m. All devices (100%) were detached from the birds and successfully retrieved. No adverse effects were detected in the birds after the tagging period, and all birds remained in their territories. This methodology can be highly useful for studies involving lightweight and elusive fauna. Additionally, our system reduces stress on individuals by minimizing the number of captures required, while also lowering human resource costs, as a single person can carry out the entire process.